A revision of the genus Sierraphytoptus Keifer 1939 (Eriophyoidea, Phytoptidae) - Chetverikov, Philipp E.; Sukhareva, Sogdiana I. (Zootaxa, 2009)
Comparative analysis of the eriophyoid mites of the genus Sierraphytoptus Keifer 1939 (= Fragaricoptes Roivainen, 1951) (Phytoptidae: Sierraphytoptinae: Sierraphytoptini) living on strawberry (Fragaria spp.) found that they are represented by two species: Sierraphytoptus setiger (Nalepa, 1894) (= Phyllocoptes setiger Nalepa, 1894) and Sierraphytoptus ambulans sp. n. Sierraphytoptus setiger forms red galls on the leaves of Fragaria viridis Duch., whereas the vagrant species S. ambulans causes no visible damage and lives mostly on the lower leave surface of Fragaria vesca L. but sometimes on F. viridis also. A supplementary description of S. setiger from North-West Russia and a key to all species of the tribe Sierraphytoptini are given. A new combination Austracus taiwanensus (K.-W. Huang 2006) comb. n. (removed from the genus Sierraphytoptus) is proposed.